Literature Review: Hubungan Depresi dengan Kadar HbA1c pada Pasien Diabetes Melitus Tipe 2 - Diah Mutia Rahmawati; Sherly Limantara; Dona Marisa; Roselina Panghiyangani (Homeostasis, 2022)
Abstract: Diabetes mellitus patient tends to be at greater risk of suffering depression. Depression on diabetes patient results in poor glycemic and metabolic control, thus affecting the patient’s HbA1c level. This literature review study was made to know the correlation between depression and HbA1c level of type 2 diabetes mellitus patient. The literature search was conducted on Pubmed-MEDLINE and Google Scholar database. Furthermore, the articles used were acquired from several researches from other institutes in Indonesia. The articles used were written in either English or Indonesian, published between 2008-2020. The result of this literature review study showed that type 2 diabetes mellitus significantly caused depression to the sufferer. The result of this literature review study also found out that the depression in type 2 diabetes mellitus patient affects the HbA1c level. Keywords: depression, HbA1c, type 2 diabetes mellitus Abstrak: Pasien diabetes melitus cenderung lebih beresiko mengalami depresi. Depresi pada pasien diabetes berakibat pada kontrol glikemik dan metabolik yang buruk, sehingga berimbas pada kadar HbA1c pasien. Literature review ini ditulis untuk mengetahui hubungan depresi dengan kadar HbA1c pada pasien diabetes melitus tipe 2. Penelusuran literatur dilakukan pada database Pubmed-MEDLINE dan Google Schoolar. Selain itu, artikel-artikel yang digunakan juga diperoleh dari beberapa penelitian pada institut lain dari Indonesia. Adapun artikel yang digunakan adalah artikel yang ditulis dalam bahasa Inggris dan Indonesia yang diterbitkan antara tahun 2008-2020. Hasil literature review, diabetes melitus tipe 2 secara signifikan menimbulkan depresi pada penderita. Pada hasil literature review juga, depresi pada pasien diabetes melitus tipe 2 dapat mempengaruhi kadar HbA1c. Kata-kata kunci: depresi, HbA1c, diabetes melitus tipe 2